Influence of Financial Management Skills on Performance of Youth Environmental Projects: A Case of Solid Waste Management Projects in Nairobi County, Kenya - Wanjiru, Nderitu B.; Kyalo, Dorothy Ndunge; Mulwa, Angeline Sabina; Mbugua, John (European Scientific Journal, ESJ, 2020)
With the upsurge of unemployment, more youths are conducting garbage collection activities as an enterprise to improve their livelihood. This study examined the influence of financial management skills on performance of youth environmental projects in Nairobi County, a case of solid waste management projects. It was guided by pragmatism research paradigm adopting descriptive survey and correlational research designs. The study’s target population was 700 youth group members engaged in solid waste management projects in Nairobi County, using a sample size of 248 group members, based on Krejcie and Morgan’s sampling table. Key informants from 4 departments of Directorate of Youth affairs were purposely selected. Research instruments entailed questionnaires and interview guide. Qualitative data was analyzed and presented in narrative statements while inferential statistics were analyzed using Pearson correlation coefficient and multiple regression analysis to test hypotheses. The correlation index between financial skills and performance of youth environmental projects was positive and significant, r (247) =.525; p≤.05. This inferred that as the level of financial project management skill increases, the performance levels also increase. The T value for financial management skills was also significant; T (247) = 9.682; β= 0.724.; P≤.05. This implied that for each unit increase in financial management skills, the performance of youth environmental projects could increase by 0.724 units. This inferred the rejection of null hypothesis and the conclusion made that H1 (There is a significant influence of financial management skills on performance of youth environmental projects in Nairobi County). The researcher recommends the pulling together of a common funding accessible to all youths by the government of Kenya and a policy action by the government to incorporate youths to learn financial management skills under mentorship programs from entities dealing with environmental projects so as to incubate their skills for effective project performance.